Syn-kinematic inversion in an intracontinental extensional field? A structural analysis of the Waterberg Thrust, northern Namibia - Granath, James; Wanke, Ansgar; Stollhofen, Harald (Journal of Structural Geology, 2022)
A structural analysis of a key area along the Waterberg Thrust in northern Namibia clarifies its geometric and timing relationships to the deposition of rift-related Karoo sediments. The fault brings late Precambrian crystalline rocks up against Permo-Triassic and Lower Jurassic Karoo clastic sediments of the Waterberg Basin between two of the major regional basement-rooted lineaments that cut across northern Namibia, using those subparallel lineaments as transfer faults. Detailed mapping and kinematic analysis have been used to construct and restore several sections across the thrust that put initiation of reverse offset as a thrust in Triassic time. Thinskinned footwall deformation created several unconformities in a footwall cutoff system. The unconformities were subsequently folded during continued motion on the fault. Various dating techniques constrain the initiation of contractional deformation to the Triassic to Jurassic (Karoo time) with episodic progression during the development of the basin, followed by major further reactivation during regional uplift related to the Atlantic margin rifting and subsequent continental breakup. This early phase is linked in time so closely to the basin development that we attribute the driver of inversion to be kinematically linked to the displacement field of Neoproterozoic basement blocks themselves. Hence, we term this relationship as ‘syn-kinematic’ to distinguish it from wholly external, superimposed driving mechanisms (‘allo-kinematic’).<br
Keywords: Waterberg thrust; Karoo tectonics; Namibia geology; Inversion tectonics; Intraplate tectonics